Global organic and inorganic aerosol hygroscopicity and its effect on radiative forcing - Mira L. Pöhlker; Christopher Pöhlker; Johannes Quaas; Johannes Mülmenstädt; Andrea Pozzer; Meinrat O. Andreae; Paulo Artaxo; Karoline Block; Hugh Coe; Barbara Ervens; Peter Gallimore; Cassandra J. Gaston; et al. (Nature Communications, 2023)
Abstract The climate effects of atmospheric aerosol particles serving as cloud condensation nuclei (CCN) depend on chemical composition and hygroscopicity, which are highly variable on spatial and temporal scales. Here we present global CCN measurements, covering diverse environments from pristine to highly polluted conditions. We show that the effective aerosol hygroscopicity, κ, can be derived accurately from the fine aerosol mass fractions of organic particulate matter (ϵ org) and inorganic ions (ϵ inorg) through a linear combination, κ = ϵ org ⋅ κ org + ϵ inorg ⋅ κ inorg. In spite of the chemical complexity of organic matter, its hygroscopicity is well captured and represented by a global average value of κ org = 0.12 ± 0.02 with κ inorg = 0.63 ± 0.01 as the corresponding value for inorganic ions. By showing that the sensitivity of global climate forcing to changes in κ org and κ inorg is small, we constrain a critically important aspect of global climate modelling.